(untitled) (Bangladesh Journal of Plant Taxonomy, 2016)
Plagiopteron Griff. (Celastraceae), collected from Bac Giang Province of Vietnam is reported here as a new generic record for the flora of Vietnam. It is supposedly an early derived member of the subfamily Hippocrateoideae (composed of tribes Campylostemoneae and Hippocrateeae), within Hippocrateaceae. The genus differs from other members of Celastraceae by its many bicyclically arranged stamens. Leaf anatomical studies have been performed to understand various features such as venation, vascular bundles, collenchyma and stomata. Taxonomic notes, description, and photographs are provided, together with short notes on the distribution, ecology and phenology of the species. Bangladesh J. Plant Taxon. 23(2): 161-166, 2016 (December)